A nationwide seroepidemiology of hepatitis C virus infection in South Korea. (29th January 2013) - Kim, Do Young; Kim, In Hee; Jeong, Sook‐Hyang; Cho, Yong Kyun; Lee, Joon Hyoek; Jin, Young‐Joo; Lee, Don; Suh, Dong Jin; Han, Kwang‐Hyub; Park, Neung Hwa; Kang, Ha Yan; Jung, Young Kul; et al.
Abstract Background & Aims The aim of this study was to reveal nationwide seroprevalence of HCV infection in South Korea by a large‐scale survey. Methods From January to December 2009, a total of 291 314 adults underwent health check‐up in 29 centres nationwide. The data concerning anti‐HCV antibody and biochemical tests were obtained from all participants. Among subjects with positive anti‐HCV, such data as HCV RNA, genotypes and treatment detail were additionally analysed. Results Using an estimated 2009 population of Korea, the age, sex and area‐adjusted anti‐HCV positive rate was 0.78%. Anti‐HCV prevalence in female patients (0.83%) was higher than that in male patients (0.75%). Gradual increase in anti‐HCV positivity was observed, from 0.34% in those aged 20–29 years to 2.31% in those >70 years. The age‐ and sex‐adjusted anti‐HCV prevalence varied in different areas, being higher in Busan and Jeonnam (1.53–2.07%), mid‐level in Seoul and surrounding districts (0.50–0.61%) and lower in Jeju (0.23%). The comparative analysis of laboratory variables between anti‐HCV (+) and anti‐HCV (−) group revealed significantly higher levels of alanine aminotransferase and lower levels of serum lipids in anti‐HCV (+) group. Among 1 718 anti‐HCV positive subjects, serum HCV RNA was measured only in 478 people, of whom 268 (56.1%) patients had detectable HCV RNA in serum. Among 50 patients for whom assessment of response to antiviral therapy was feasible, overall sustained virological response was achieved in 84% of patients. Conclusion The prevalence of HCV infection is low in South Korea. Studies to analyse risk factors are warranted to reduce HCV infection.